Chinese athletes and parents’ motivations for U.S. Collegiate sports participation - Sun, Wenting; Ravert, Russell D.; Sethi, Simran K. (Journal of International Students, 2026)
To gain an understanding of international student recruitment and retention in collegiate athletics, this study examines the motivations and decision-making processes of Chinese high school athletes and their parents in pursuing U.S. collegiate sport opportunities. Using the push–pull framework and an ecological perspective, it explores how individual aspirations, family priorities, institutional resources, and national policies shape transnational mobility. Semistructured focus group discussions with 10 athletes and eight parents revealed six key motivational themes and highlighted the influence of recent collegiate sport-related policy changes in China. The findings suggest that while both groups value U.S. sport pathways, athletes and parents may hold different motivations and expectations.